Penyelarasan Sistem Tata Kelola pada PT. MEI dengan Menggunakan Cobit 2019 - Insan Kamaludin Arifin; Tukino Tukino; Fitria Nurapriani; Saepul Aripiyanto (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2022)
PT. MEI is a consulting company providing human resources and management of human resource functions, one of the programs implemented is the Domestic Apprenticeship program, to carry out these business processes. PT. MEI already has an information system but it is not optimal and is named (Apprenticeship Administration Information System). Therefore the use of COBIT Design Toolkit 2019 aims to help PT. MEI in aligning the governance system so that it is well mapped and ensures that IT achievements are aligned with the management and business environment in the company. This study aims to design a Governance Design based on the 2019 Cobit Design Toolkit The method used is to utilize the Cobit 2019 design factor, this study produces recommendations for the use of the priority core model and the competency level of PT. MEI The results of this study will be based on 31 core models or processes that need to be run with level 1 capabilities, two core samples or processes that need to be run with level 2 capabilities, four core models or processes that need to be run with level 3 capabilities, and two models or core competency processes that need to be implemented with competency level 4. Companies must conduct an assessment of the main point stage model According to the results of this study to ensure that business processes operate optimally. The core model evaluation phase must be done by level of importance put forward by the 2019 COBIT design factors as a follow-up to the findings of this study.